Curcumin inhibits the invasion and metastasis of triple negative breast cancer via Hedgehog/Gli1 signaling pathway. (30th January 2022) - Li, Mengjie; Guo, Tingting; Lin, Jiayi; Huang, Xia; Ke, Qiaodan; Wu, Yujian; Fang, Chunping; Hu, Chenxia
Abstract: Ethnopharmacological relevance: In traditional Chinese medicine, there is a long history that curcuma longa L is used to treat distending pain of chest and belly, arthralgia of shoulder and arm aggravated by cold. Traditional Chinese medicine holds that breast cancer is caused by cold congelation, stagnation of qi and blood stasis. It is usually treated with some pungent and warm Chinese herbs, such as Curcuma longa L and Curcuma zedoaria (Christm.) Rosc, which are effective in promoting blood circulation for removing blood stasis, activating qi-flowing and relieving pain. Curcumin, a polyphenolic compound, is the main pharmacological component extracted from the rhizome of Curcuma longa L. Modern pharmacological studies have found that curcumin has many kinds of pharmacological activities of anti-inflammatory, anti-tumor, anti-angiogenesis, anti-metastasis and anti-multidrug resistance. Aim of the study: To explore the mechanism of curcumin and Glioma-associated oncogene homolod-1 (Gli1) on invasion and metastasis of triple negative breast cancer (TNBC) cells through the Hedgehog (Hh)/Gli signaling pathway. Material and Methods: The effect of curcumin on TNBC cells was detected by colony formation, wound healing and transwell assay. Breast cancer stem cells (BCSCs) were cultured in serum-free medium and its stemness was detected by flow cytometry and subcutaneous xenografted tumor assay. The formation of mammospheres was used to detect the effect of curcumin and GANT61 (Gli inhibitor)on the formation ability of BCSCs. Gli1 overexpressed was conducted in MDA-MB-231 cells by lentivirus vector HBLV-h-Gli1-3xflag-ZsGreen-PURO. RT-qPCR and Western blot were detected the mRNA and protein level of genes of Hh pathway, Epithelial-mesenchymal transition (EMT) and stemness. The nuclear localization and expression of Gli1 was observed by laser confocal microscope scanning. Co-IP was investigated the key genes interacted with Gli1. Results: The abilities of proliferation, invasion, migration and the formation of mammospheres in TNBC cells were inhibited by curcumin. Furthermore, curcumin reduced the invasion and migration abilities in stable Gli1-overexpressing MDA-MB-231 cell. Moreover, curcumin down-regulated the expression of genes related Hh pathway, EMT and stemness in MDA-MB-231 mammospheres. Observation of laser confocal microscope showed that Gli1 were expressed mainly in nucleus in MDA-MB-231 adherent cells and completely in nucleus in BCSCs, which was significantly reduced in the nucleus and cytoplasm after curcumin treatment. Besides, our results suggested that vimentin was interacted with Gli1. Conclusions: Curcumin can inhibit the proliferation and metastasis of TNBC cells, EMT and characteristics of BCSC by Hedgehog/Gli1 pathway. Graphical abstract: Image 1 Highlights: Curcumin can inhibit the proliferation and metastasis of TNBC cells, EMT and characteristics of BCSCs. Curcumin inhibited Hh pathway by reducing the expression of Gli1 in nucleus.Gli1may be an effective target of curcumin. Dysregulation of Gli1 induced the expression of vimentin, thus effecting the process of EMT and characteristics of MDA-MB-231 BCSCs.